A Critical Discourse Analysis of Selected Pakistani Novels - Rasheed, Saba; Kashif, Farah; Kazmi, Sheeza (Annals of Human and Social Sciences, 2023)
This research paper conducts a critical discourse analysis of two Pakistani novels, namely "Home Boy" by H. M. Naqvi and "The Blind Man’s Garden" by Nadeem Aslam. The primary objective is to gain an insider’s perspective on the ideological frameworks and power dynamics within these texts through a comparative analysis. The study explores the language used in the novels to observe shifts in the political system, with a specific focus on evaluating American public rhetoric and prevailing discourse post-September 11. The qualitative research utilizes purposively sampled data from post-9/11 literature by Pakistani writers, employing Van Dijk’s Socio-Cognitive approach of Critical Discourse Analysis (CDA) to analyze the selected data. This approach emphasizes the cognitive dimensions of discourse interpretation and development. The findings of the study reveal a notable shift in political and social discourse after 9/11, characterized by stereotypical attitudes, ethnic prejudice, cultural variations, power abuse by elites, and resistance by dominated groups. The novels illustrate that Muslims become victims and legitimate targets of hate crimes, derogatory media perceptions, disappearances, physical beatings, and racial discrimination post-9/11. The research also observes how assimilation transforms into alienation, focusing on the characters in the novels. Additionally, the paper discusses the general social representation, including knowledge, attitudes, beliefs, norms, values, and ideologies of language users in the context of the analyzed novels.